Estimación de volatilidades y pronóstico en los precios del atún y camarón de exportación ecuatoriano periodo 2010-2020 - Toapanta Chancusig, Sandy Lisbeth (2024)
ABSTRACT: The main objective of this work is to identify the volatility and forecasts of the prices of tuna and shrimp for export in Ecuador. Due to this, applying the Autoregressive Models of Conditional Heteroskedasticity ARCH and GARCH was necessary. According to empirical experience, these models serve to contrast periods of significant continuous error variance with others of smaller variance. That is, the value of the dispersion of the error concerning its mean changes in the past. Therefore, it is natural to think that a model that considers the prediction of the values of said variance in the past will serve to make more precise estimates. An analysis of the prices of the mentioned products, which were obtained from the database of the National Chamber of Aquaculture and the Central Bank of Ecuador for the period 2010- 2020, was carried out. In this way, the study focuses on estimating volatilities through the ARCH and GARCH models with their respective validation considering the best parameters for each variable: tuna and shrimp prices. The results show that the ARCH model is the most efficient for forecasting the tuna price trend, while the GARCH model is more suitable for forecasting shrimp prices. In both cases, a growth trendis observed for subsequent periods.